Kewajiban Menuntut Ilmu: Upaya Mengembangkan dan Mengamalkan untuk Kehidupan Bermakna - Yulinda; Luthfiyah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to examine the concepts of the obligation to seek knowledge, the advancement of knowledge, and the application of knowledge from the perspective of Islamic teachings. The study employed a qualitative approach using the library research method. Data were collected from the Qur’an, Hadith, classical Islamic scholarly works, and relevant scientific literature, and were analyzed using qualitative descriptive analysis. The findings reveal that Islam positions knowledge as a fundamental element in human development and civilization, encompassing spiritual, intellectual, and social dimensions. The obligation to seek knowledge is viewed as both an individual and collective responsibility that supports personal growth and societal welfare. Furthermore, the development of knowledge in Islam emphasizes the integration of faith, reason, and ethical values, while the application of knowledge serves as a means of fulfilling religious responsibilities and contributing to the common good. The study concludes that the obligation to seek knowledge, its development, and its application constitute an interconnected framework that shapes the character, responsibility, and holistic development of Muslims.